CGIAR Nutrition Impact Platform Tribute to Dr. M. S. Swaminathan - Wismen, Bendula; Pizarras, Charlotte; Thilsted, Shakuntala (CGIAR Impact Platform on Nutrition, Health and Food Security, 2025)
CGIAR Nutrition Impact Platform produced and screened this video in the ‘From Feeding the Hungry to Nourishing All People: A Tribute to Dr. M. S. Swaminathan’ event during World Food Prize Week of Events 2024.Video creator: Charlotte Pizarras, October 2024